De la ciencia a la acción: Desafíos para América Latina en 2025 (SciComm Report, 2025)
The year 2025 started with record temperatures in several regions of Latin America, an alarming reminder that the climate crisis is not a problem of the future, but it is here and it is moving The pace of change is faster than many expected. The heat waves, especially in Chile havethe social inequities and the great structural challenges to address the country’s impact of climate change. At the same time, we the latent risk of forest fires highlights the urgency of strengthening communities' resilience to natural disasters, which are The most frequent and devastating.
Keywords: Science, Citizenship and Communication; Latin America; climate change; planetary health; artificial intelligence; communication of science